Estimation of influenza activity in Vojvodina (Serbia) for five consecutive influenza seasons - Ristić, Mioljub; Štrbac, Mirjana; Medić, Snežana; Petrović, Vladimir (Vojnosanitetski pregled, 2020)
Background/Aim. After pandemic 2009/10 influenza season, influenza A (H1N1)pdm09, A(H3N2) and B viruses have continued to circulate in the population. The aim of this study was to describe the epidemiological and virological characteristics of influenza and evaluate values of proposed case definitions of influenza like illness (ILI), severe acute respiratory illness (SARI) and acute respiratory distress syndrome (ARDS) for detecting laboratory-confirmed influenza cases in Vojvodina. Methods. We conducted a descriptive epidemiological study using surveillance reports and laboratory data from October 2010 to May 2015 (five surveillance seasons). Results. Out of 1,466 samples collected, 720 (49.1%) were laboratory confirmed as influenza. Influenza A infection was more frequently detected than influenza B infection. Using the case definition of ILI was a good predictor for influenza confirmation (p < 0.05) during 5 influenza seasons. The predominant age-range of patients with confirmed influenza A (42.2%) and B (43.0%) infections was 30 to 64, but the patients aged from 15 to 29 years were more likely to have influenza A (p = 0.0168). In the period from December to January, influenza A (17.8%) was more frequently registered than influenza B (7.6%). The highest number of deaths (19/38) and hospitalized patients (128/402) was registered during the last influenza season (2014/15). The immunosuppressed patients with confirmed influenza infection were more likely to have influenza B than influenza A (p = 0.0110). Conclusion. Our results indicate that influenza surveillance should be continued and expanded in order to fully assess the burden of the disease in given population.